Fandom as Methodology A sourcebook for artists and writers - Grant, Catherine; Random Love, Kate (Goldsmiths Press, 2019)
This highly visual history of women's cycle wear brings together Victorian engineering, patent studies and radical feminist invention. Underpinned by three years of in-depth archival research and inventive practice, this new book by Kat Jungnickel and Goldsmiths Press brings to life in rich detail the lesser-known stories of six inventors and their unique contributions to cycling's past which continue to shape urban life for contemporary mobile women.